Upcycling marine food waste into biodegradable food packaging: a sustainable approach toward zero-waste society and biocircular economy - Dissanayake, Kasun Kumara; Kurniawan, Tonni Agustiono; Sarangi, Prakash Kumar; AlSultan, G. Abdulkareem; Goh, Hui Hwang; Wong, Hin Yong; Onn, Choo Wou; Tharikulislam, Mohamed; Aziz, Faisal; Othman, Mohd Hafiz Dzarfan; Anouzla, Abdelkader; Ali, Imran; et al. (Elsevier, 2026)
Seafood processing creates a large amount of waste, with 50 %–75 % of the seafood processed discarded as byproducts or waste that often ends up in landfills, releasing methane. This study explores converting marine food waste—such as seaweed residues and crustacean shells—into biodegradable food packaging, addressing both food waste and plastic pollution. Turning marine food waste into biodegradable packaging can help solve environmental and economic challenges. The plastic packaging industry generates over $350 billion annually; yet, less than 10 % of plastic waste is recycled, underscoring the need for improved resource management. Chitosan from crustacean shells offers an oxygen barrier 50 % more effective than typical plastics, while biopolymers from algae—like alginate, carrageenan, and agar—can biodegrade 90 % within 30 days. Combining chitosan with algae and seaweed derivatives supports the sustainable production of high-performance containers. However, the bioplastics industry faces major challenges: production costs are four times higher than conventional plastics, and market and regulatory hurdles are also four times greater. Using marine food waste biopolymers in packaging could help industries reduce landfill waste and promote circular economy efforts each year. Widespread adoption depends on resolving three main issues: production costs, scalability, and regulatory approval.